Guidelines for the Use of Non-Standard Road Signs – Polish Experiences - Alessandro Calvi; Stanisław Gaca; Tomasz Kamiński; Mariusz Kieć; Mikołaj Kruszewski (Archives of Civil Engineering, 2021)
The aim of the paper is to present the procedure of non-standard road signs and markings implementation in Poland to improve road safety and traffic performance of road infrastructure. The authors investigated the following cases: road and its surroundings’ perception and understanding improvement; warning of increased risk of accidents ; road works; speed management and ITS. The procedure was developed on the basis of interdisciplinary research, including: observation of drivers behaviour in real traffic; comparative crash analysis on sections with and without non-standard signs or markings; surveys on the understanding signs and marking; driving simulator experiments. As a result of the research, an implementation procedure for non-standard signs and markings, in the form of flowchart, was developed. In the designed procedure the following study of non-standard signs can be distinguished: questionnaire studies, eye tracking tests and driving simulator tests. The choice of the test method depends on the preliminary assessment of sign understanding, based on the results of the questionnaires. Moreover, thresholds for the declared understanding level, which determines the selection of additional tests to be done prior to the implementation of the sign, are given. The guidelines for conducting tests, analysis and monitoring of implementation were described as well.